The Stalinist dictatorship - Ward, Chris 1948- (Arnold Readers in history, 2016)
The Soviet thermidor / L.D. Trotsky -- Stalin in focus / T.H. von Laue -- The decisive trifle / R.C. Tucker -- Stalin's mind / D. Volkogonov -- The 'Great Change' / I. Deutscher -- The politics of repression revisited / J. Arch Getty -- A debate on collectivization: was Stalin really necessary? / J.R. Millar and A. Nove -- Society, state, and ideology during the first five-year plan / M. Lewin -- Bab'i bunty and peasant women's protest during collectivization / L. Viola -- Stakhanovites in the cultural mythology of the 1930s / L.H. Siegelbaum -- The omnipresent conspiracy: on Soviet imagery of politics and social relations in the 1930s / G.T. Rittersporn -- How the mice buried the cat: scenes from the great purges of 1937 in the Russian provinces / S. Fitzpatrick -- The family, the school, the church: the pillars of society shaken and re-enforced / N.S. Timasheff -- New protagonists / V.S. Dunham.